2022
DOI: 10.3390/agriculture13010082
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Mechanism of Papaver rhoeas ALS Inhibitors Resistance in Poland

Abstract: Herbicide resistance in weeds, including corn poppy (Papaver rhoeas L.), is an increasing problem compromising global crop production. The aims of this study were to evaluate the susceptibility of P. rhoeas populations in Poland to acetolactate synthase (ALS) inhibitors and elucidate their mechanisms of resistance. Between 2017 and 2020, 157 seed samples were collected nationwide and a dose-response study with various ALS-inhibiting herbicides was performed in glasshouses. This revealed 14 resistant population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…Leu197 and Ser197 were the most frequent and widespread alleles, while Ala197 was present in a significantly lower number of populations, on par with Leu574 (Table 1). This contrast was also observed within and among previous studies 15,18,19,23–26 . However, when assaying ALS isoforms identical bar the amino‐acid at codon 197, we found that the enzymatic properties of isoform Ala197 were closest to those of the wild‐type ALS isoform, and that its resistance pattern was similar to that of isoform Ser197.…”
Section: Discussionsupporting
confidence: 77%
See 4 more Smart Citations
“…Leu197 and Ser197 were the most frequent and widespread alleles, while Ala197 was present in a significantly lower number of populations, on par with Leu574 (Table 1). This contrast was also observed within and among previous studies 15,18,19,23–26 . However, when assaying ALS isoforms identical bar the amino‐acid at codon 197, we found that the enzymatic properties of isoform Ala197 were closest to those of the wild‐type ALS isoform, and that its resistance pattern was similar to that of isoform Ser197.…”
Section: Discussionsupporting
confidence: 77%
“…This contrast was also observed within and among previous studies. 15,18,19,[23][24][25][26] However, when assaying ALS isoforms identical bar the amino-acid at codon 197, we found that the enzymatic properties of isoform Ala197 were closest to those of the wildtype ALS isoform, and that its resistance pattern was similar to that of isoform Ser197. Conversely, the isoforms encoded by the widespread and frequent Leu197 and His197 alleles had a greatly reduced affinity for the ALS substrate and cofactors (Fig.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations